1959
DOI: 10.1084/jem.110.4.495
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON BLOOD FACTORS RhA, RhB, AND RhC

Abstract: In a series of papers (1-3), clinical cases of hemolytic transfusion reaction and erythroblastosis fetalis have been reported involving patients with Rh-positive blood (two with standard P, h0 factor, one with Rh0 variant factor) who had become sensitized and produced antibodies resembling anti-Rh0 in specificity. Similar cases had been encountered by other observers (4--6). Since the antibodies in our patients' serums were shown to be different from anti-PJao and from one another, they have been assigned the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1960
1960
1993
1993

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…The results confirm previous find ings [3] that structural abnormalities of D may be accom panied by a reduced expression in the number of available sites. One example of the category IVa cells showed a considerable reduction compared to the other 4 examples and the numbers of sites on cells of categories Va and VI The number of available sites which reacted with the Los-2 antibody were on average only 50% of the values given by Brad-3 (table 1), suggesting that there is also some steric hindrance of access to this epitope by neigh bouring molecules [14].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results confirm previous find ings [3] that structural abnormalities of D may be accom panied by a reduced expression in the number of available sites. One example of the category IVa cells showed a considerable reduction compared to the other 4 examples and the numbers of sites on cells of categories Va and VI The number of available sites which reacted with the Los-2 antibody were on average only 50% of the values given by Brad-3 (table 1), suggesting that there is also some steric hindrance of access to this epitope by neigh bouring molecules [14].…”
Section: Resultssupporting
confidence: 91%
“…It was assumed that part of the D antigen was missing in these recipients. In many of these latter individuals there is also a reduction in the number of abnormal D molecules expressed on the cells and thus they can also be classified under the descrip tive term Du [3], This has led to problems in nomencla ture.…”
Section: Introductionmentioning
confidence: 99%
“…Wiener has classified these into four sub groups A, B, C and D [8,9] and Tippett has offered another classification which distinguishes six categories, each identified by a Roman numeral [7]. Individuals whose red cells are typed as Rh0-positive but lack any one of these components may become immunized to the missing part.…”
mentioning
confidence: 99%
“…Since Unger et al [2] has shown that the factor DB (Rh0B) is present in most Rhesus positive poeple, it would appear that DB (Rh0B) is less antigenic than some of the other D (Rh0) factors.…”
mentioning
confidence: 98%